2017
DOI: 10.1038/s41391-017-0030-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum cholesterol and risk of high-grade prostate cancer: results from the REDUCE study

Abstract: BackgroundEpidemiologic evidence for a serum cholesterol-prostate cancer link is mixed. Prostate-specific antigen (PSA) is positively correlated with cholesterol, potentially increasing PSA-driven biopsy recommendations in men with high cholesterol, though biopsy compliance may be lower in men with comorbid conditions. These potential biases may affect PSA-driven biopsy rates and subsequent prostate cancer detection in men with high serum cholesterol. Our objective was to test the association between serum cho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
80
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(85 citation statements)
references
References 27 publications
3
80
0
2
Order By: Relevance
“…As pointed out by Dr Kawada, our previous studies have linked elevated serum high‐density lipoprotein (HDL) with worse PCa outcomes. Concordantly, previous studies have also linked elevated HDL with increased risk of advanced PCa and high‐grade PCa . Therefore, despite HDL being a protective factor against atherosclerosis and cardiovascular disease, in PCa its role appears to be quite different.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…As pointed out by Dr Kawada, our previous studies have linked elevated serum high‐density lipoprotein (HDL) with worse PCa outcomes. Concordantly, previous studies have also linked elevated HDL with increased risk of advanced PCa and high‐grade PCa . Therefore, despite HDL being a protective factor against atherosclerosis and cardiovascular disease, in PCa its role appears to be quite different.…”
supporting
confidence: 57%
“…Concordantly, previous studies have also linked elevated HDL with increased risk of advanced PCa 2 and high-grade PCa. 3 Therefore, despite HDL being a protective factor against atherosclerosis and cardiovascular disease, in PCa its role appears to be quite different. In PCa the amount of cholesterol available to cancer cells from the serum may be more important than the distribution of cholesterol subtypes.…”
mentioning
confidence: 99%
“…Likewise, hypertriglyceridaemia showed a weak positive but non-significant association with prostate cancer. On the other hand, HDL has been shown also to significantly correlate with high-grade prostate cancer at diagnosis, as shown in the post hoc analysis of the REduction by DUtasteride of prostate Cancer Events (REDUCE) study [15]. Besides a potential role in prostate cancer diagnosis, a serum lipogram has been shown to have prognostic value post-RP.…”
Section: Discussionmentioning
confidence: 96%
“…However, prostate cancer often becomes resistant to such treatments (29). The effects of HDL on prostate cancer development and progression are controversial, with both positive and inverse associations found in various studies (2)(3)(4)(5). A meta-analysis of 14 large prospective studies found no significant effect of HDLcholesterol on the risk of prostate cancer (30).…”
Section: Discussionmentioning
confidence: 99%
“…Prostate cancer is the most common malignancy and second leading cause of cancer-related deaths among men in the United States (1). The association of HDL levels with prostate cancer risk has been inconsistent, with some studies showing a positive association (2,3) some showing an inverse association (4,5), and others showing no association (6,7). HDL biogenesis is mediated by ATP-binding cassette transporter A1 (ABCA1), which assembles cellular lipids with exogenous lipid-poor apolipoprotein A1 (apoA1) to generate nascent HDL (8).…”
mentioning
confidence: 99%